The Development of Edmodo on Immune System Material to Train Critical Thinking: Validity and Student Responses - Savira Eka Yuli Agustina; Nur Qomariyah (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2022)
The spread of Covid-19 continues to increase, causes the government to issue policies that can supress this spread. One of the policies in educational field is distance learning. The distance learning is helped out by technology development, but it requires student to think at a high level such as critical thinking. Critical thinking skills can be trained in biology. The material that need critical thinking skills is immune system. In fact, immune system material is considered difficult and the result of national exam show only 25.19% of student can complete this material. Therefore, it is necessary to have learning media that can facilitate the achievement of basic competency and critical thinking skills. This research aims to produce Edmodo that equipped with student worksheets to train critical thinking skills. This research is development research with 4D Model (Define, design, develop, disseminate). It was limited to the development stage to determine the validity of product based on expert opinion and also the practicallity based on the responses of eleventh grade student in SMA Negeri 1 Waru Sidoarjo. Quantitative descriptive analysis was applied for the data gained. The result showed the validity of Edmodo were 3.88 on presentation aspect, 3.91 on content, and 3,89 for the total average. The student worksheet validity resulted were 3.90 on presentation, 3.95 on content, 3,89 on language, 3.67 on critical thinking, and 3,85 for the total average. Both of them are categorized as very valid. The results of student responses are 88.03% in the very practical category. Thus, the development of Edmodo and student worksheet is valid and practical to used in lerning. Keywords: Edmodo, student worksheets, immune system, critical thinking skills